2009
DOI: 10.1242/jeb.033340
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound detection in the Gulf menhaden requires gas-filled bullae and an intact lateral line

Abstract: SUMMARYClupeiform fish species, including the Gulf menhaden (Brevoortia patronus) that belong to the subfamily Alosinae, can detect ultrasound. Clupeiform fishes are unique in that they have specialized gas-filled bullae in the head associated with the ear via the bulla membrane and with the lateral line via the lateral recess membrane. It has been hypothesized that the utricle of the inner ear is responsible for ultrasound detection through a specialized connection to the gas-filled bullae complex. Here, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Higgs et al (2004) found that the middle macula of the utricle (see Figure 5F) is more loosely connected to the rest of the utricle in the American shad A. sapidissima and presumably vibrates more compared with species that do not detect ultrasound. Wilson et al (2009) showed experimentally that the gas-filled bullae and their attachment to the lateral line are responsible for ultrasonic hearing in the Gulf menhaden B. patronus. The prootic bullae are positioned closer to the body surface in B. patronus.…”
Section: Osteoglossomorpha: Notopteridae (Knifefishes) and Clupeidae mentioning
confidence: 99%
“…Higgs et al (2004) found that the middle macula of the utricle (see Figure 5F) is more loosely connected to the rest of the utricle in the American shad A. sapidissima and presumably vibrates more compared with species that do not detect ultrasound. Wilson et al (2009) showed experimentally that the gas-filled bullae and their attachment to the lateral line are responsible for ultrasonic hearing in the Gulf menhaden B. patronus. The prootic bullae are positioned closer to the body surface in B. patronus.…”
Section: Osteoglossomorpha: Notopteridae (Knifefishes) and Clupeidae mentioning
confidence: 99%
“…The association between special sensory epithelia and enhanced hearing is strengthened by observations in herrings and relatives (the clupeids), where the utricle is involved in hearing and provides a wide hearing bandwidth. In these species, unlike all other studied vertebrates, the utricular epithelium is highly derived and may, in fact, be associated with detection of ultrasound to over 180 kHz in one clupeid group, the Alosinae (Mann et al, 1997;Higgs et al, 2004 e although see Wilson et al (2009) for recent experiments that suggest that the lateral line system is involved in ultrasound detection).…”
Section: Epithelial Hair Cell Organizationmentioning
confidence: 99%
“…Wilson et al (2009) investigated in what way this accessory hearing structure contributes to sensitivity to ultrasound in the Gulf menhaden. Filling the gas-filled bullae with Ringer solution reduced the response of the auditory system to 40 kHz tone bursts measured by the AEP technique indicating that the air-filled bullae are necessary for ultrasonic hearing.…”
Section: Using Aep-technique To Investigate Accessory Hearing Structuresmentioning
confidence: 99%